OPTIMALIZATION ON BALL BOUNDARY WITH NONMONOTONE GRADIENT PROJECTION METHOD - MARWANSYAH (10110084), DEDI
Constrained optimization is an optimization process that used to optimizing either minimize or maximize value of objective function that holds the constrains. In this final assignment will discuss about minimizing value of objective function on ball boundary with nonmonotone gradient projection method, and its objective function is a quadratic convex function. On this method, every point x that generated every iteration will be projected on ball boundary. This nonmonotone gradient projection method used barzilai Ã‚Â– borwein method to find descent search direction, and used adaptive two-point stepsize gradient method to find value of reference function.